(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Geriatric Depression (GD) prevalence rate is on the rise as is the geriatric population in India. It can be correlated to Kaphaja Unmada in Ayurveda based on its causes and symptoms. GD patients have symptoms like Mandavakchesta (slowing of speech and actions), Tushnibhava (depressed look), Anaannabhilasha (disinclination for food). GD has several causative factors like decreased physical agility, cognitive decline, lack of financial liberty, social isolation, long standing diseases and medicines etc. Following the surge of industrialization, urbanization like western countries after 1980s, the family systems and values in India have changed. Nuclear families are on rise and elderlies in families are considered as burden. Contrastingly, earlier elderlies were regarded as source of wisdom and guidance. This study is an attempt to go through all the possible literature offline and online to find out the causes and solutions of GD in India. Findings showed that along with the common causative factors related to the old age in elderlies, ignorance from younger family members is also equally important. GD is a psychosomatic disease, so treatments approach involving the body, mind, family dynamics and values using family psychotherapies and psychoeducation, Medhya rasayana and if needed modern psychiatric medication can address all types of GD and related mental health problems in India.